Antibacterial Activity Test of Guava Leaf Ethanol Extract against Staphylococcus epidermidis and its Formulation as Anti-Acne Serum - Tristania Magdalena Dumatubun; Senda Kartika Rakainsa (Universitas Negeri Semarang, 2024)
Skin is a layer of tissue that spreads over the entire surface of the body. On the surface of the skin, sweat glands secrete waste products through the skin pores in the form of sweat. Acne (Acne vulgaris) is a condition where the pores are clogged and cause pockets of pus to become inflamed. Guava leaves (Psidium guajava L.) contain alkaloid, flavonoid, tannin, saponin and steroid compounds that are believed to have antibacterial activity. The purpose of this study was to determine the antibacterial activity of guava leaves (Psidium guajava L.) against Staphylococcus epidermidis made in serum dosage form. In this study, guava leaf extract was tested to determine the value of MIC (Minimum Inhibitory Level) using the liquid dilution method and MBC (Minimum Bactericidal Level) using the solid dilution method by measuring the diameter of the inhibition zone. The results showed that the MIC of guava leaf extract was obtained at a concentration of 0.05 while the MBC results of guava leaf extract were obtained at a concentration of 5%. Serum preparation is a low viscosity preparation that delivers active substances through the skin surface which has more active ingredients and less solvent content. Serum preparation formulations were made in several concentrations, namely F0 0%, F1 2%, F2 4%, and F3 6%. Physical evaluation of the preparation included organoleptic, homogeneity, adhesion, spreadability, pH, and viscosity. The antibacterial activity test of serum preparations was carried out by the pitting diffusion method. The results showed that F3 had the largest inhibition zone of 13 mm and was included in the strong category.